Shaping Rolling Circle Amplification Products into DNA Nanoparticles by Incorporation of Modified Nucleotides and Their Application to In Vitro and In Vivo Delivery of a Photosensitizer - Kim, Kyoung-Ran; Rothlisberger, Pascal; Kang, Seong Jae; Nam, Kihwan; Lee, Sangyoup; Hollenstein, Marcel; Ahn, Dae-Ro (MDPI, 2018)
Rolling circle amplification (RCA) is a robust way to generate DNA constructs, which are promising materials for biomedical applications including drug delivery because of their high biocompatibility. To be employed as a drug delivery platform, however, the DNA materials produced by RCA need to be shaped into nanoparticles that display both high cellular uptake efficiency and nuclease resistance. Here, we showed that the DNA nanoparticles (DNPs) can be prepared with RCA and modified nucleotides that have side-chains appended on the nucleobase are capable of interacting with the DNA strands of the resulting RCA products. The incorporation of the modified nucleotides improved cellular uptake efficiency and nuclease resistance of the DNPs. We also demonstrated that these DNPs could be employed as carriers for the delivery of a photosensitizer into cancer cells to achieve photodynamic therapy upon irradiation at both the in vitro and in vivo levels.
Keywords: PHOTODYNAMIC THERAPY; METHYLENE-BLUE; NONPORPHYRIN PHOTOSENSITIZERS; OLIGONUCLEOTIDES; CYTOTOXICITY; PORPHYRIN; CANCER; TUMORS; SIZE